Preparation of Molecularly Imprinted Polyaniline-Graphene Composite Electrodes for Detection of Dopamine - Chamari Pothipor (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Precision in quantification and accurate detection of chemical and biological species are of great attention for health care, diagnostics and environmental monitoring. The development of a simple and low-cost electrochemical platform for sensing applications with high sensitivity, good selectivity, and high stability is important. This study presents the fabrication of graphene (GP)-modified screen printed carbon electrode (SPCE). The target molecule for the detection in this study is dopamine (DA), an essential neurotransmitter involving in the central nervous system. Due to its electrochemical activity, its detection is attracting the great interests in electroanalysis. The sensitivity and selectivity of such GP-modified electrode could be improved by the electrosynthesised DA- MIPANI having artificial recognition sites. The MIPANI possess an ability to recognise closely related compounds via an artificial molecular lock and key process. The artificial receptor sites of the polymers can be shaped by imprinting the template molecules onto a polymer. After removal of the template molecules, the MIPANI film showed ability to rebind specifically to DA. Electrochemical properties of each electrode were examined by cyclic voltammetry (CV) and differential pules (DPV). The DPV result of MIPANI film on GP-modified SPCE showed that current responses displayed two linear ranges of 1.0-100 nM (R2= 0.9949) and 0.1-400 μM (R2= 0.9986). The MIPANI-GP-modified SPCE also presented the low limit of detection (3S/N, n = 3) of 0.190 nM. Therefore, the development of the electrodes is promising for advanced electrochemical sensing applications with high sensitivity, good specificity and high stability.